Testimony - Turow, Scott (New York : Grand Central Publishing, 2017)
"In the bestselling tradition of Presumed Innocent--the 1987 debut novel that made him "one of the major writers in America" (NPR)--comes what may be Scott Turow's best thriller yet... Bill ten Boom has walked out on everything he thought was important to him: his career, his wife, Kindle County, even his country. Still, when he is tapped to examine the disappearance of an entire Gypsy refugee camp--unsolved for ten years--he feels drawn to what will become the most elusive case of his career. In order to uncover what happened during the apocalyptic chaos after the Bosnian War, Boom must navigate a host of suspects ranging from Serb paramilitaries to organized crime gangs to the U.S. government, while also maneuvering among the alliances and treacheries of those connected to the case: Morgan Merriwell, a disgraced U.S. Major General; Ferko Rincic, the massacre's sole survivor; and Esma Czarni, an alluring barrister with secrets to protect. A master of the legal thriller, Scott Turow has returned with his most irresistibly confounding and satisfying novel yet"--
Library Journal
Publishers Weekly
Kirkus Reviews
Library Journal Prepub Alert
Adult
Keywords: War crimes -- Fiction -- Bosnia and Herzegovina; Genocide. -- Fiction -- Bosnia and Herzegovina; Missing persons -- Fiction -- Investigation; Suspense fiction; Mystery fiction; Legal stories